2004
DOI: 10.1016/s0047-2727(03)00024-0
|View full text |Cite
|
Sign up to set email alerts
|

Using market valuation to assess public school spending

Abstract: In this paper we use a "market-based" approach to examine whether increased school expenditures are valued by potential residents and whether the current level of public school provision is inefficient. We do so by employing an instrumental variables strategy to estimate the effect of state education aid on residential property values. We find evidence that, on net, additional state aid is valued by potential residents and that school districts do not appear to overspend on education. We also find that school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 38 publications
5
83
0
1
Order By: Relevance
“…Parents with children and a higher income are willing to pay more for houses in exchange for getting the children in these high quality schools. The empirical results of this study confirmed the research results by Barrow and Cecilia (2004).…”
Section: Conclusion and Suggestionssupporting
confidence: 88%
See 2 more Smart Citations
“…Parents with children and a higher income are willing to pay more for houses in exchange for getting the children in these high quality schools. The empirical results of this study confirmed the research results by Barrow and Cecilia (2004).…”
Section: Conclusion and Suggestionssupporting
confidence: 88%
“…This suggests that school quality can significantly affect the price level of houses, Haurin and Brasington (1996) selected 29 variables (4 variables representing schools) and applied the hedonic price model for the housing market, confirming that the quality of schools in Ohio (in the United States) has a considerable impact on house prices, confirming that the distance from downtown, and the comfortableness (community crime rate, cultural arts, amusement) also have a considerable impact on house prices. Barrow and Cecilia (2004), using the District of Columbia (again, in the United States) as an empirical research region, argued that school quality is one of the major considerations when selecting a residence. Parents with a higher level of income are willing to pay higher prices in exchange for their children having the opportunity to study in a high quality school (an amount of 3,300 USD extra in exchange for an increase of 100 points in SAT (Standard Aptitude Test) 8 achievement scores).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Communities that over-or underspend relative to resident preferences will see their land values decline. Barrow and Rouse (2004) Massachusetts passed Proposition 2½ limiting local taxation to 2.5 percent of local property values.…”
Section: Governance and Valuementioning
confidence: 99%
“…The associated tax savings can be substantial: Considering the one quarter of San Francisco Bay Area families with more than 20 years of housing tenure in 1 Much of the intuition on household sorting was derived from a long line of theoretical work in local public finance that started in Tiebout (1956), and which includes Epple and Zelenitz (1981), Epple, Filimon, andRomer (1984, 1993), Benabou (1993), Fernandez and Rogerson (1996), Nechyba (1997) and Epple and Sieg (1999). 2 Recent examples are found in Barrow and Rouse (2004), Rothstein (2006) and Bajari and Kahn (2005). 3 As Rubinfeld (1987) points out "the value and usefulness of the Tiebout model is likely to diminish in the future, and an alternative or alternatives are needed."…”
Section: Introductionmentioning
confidence: 99%